The influence of African air pollution on regional and global tropospheric ozone - (:unkn) unknown (My University, 2007)
We investigate the influence of African biomass burning, biogenic, lightning and anthropogenic emissions on the tropospheric ozone over Africa and globally using a coupled global chemistry climate model. Our model studies indicate that surface ozone concentration may rise by up to 50 ppbv in the burning region during the biomass burning seasons. Biogenic emissions yield between 5?30 ppbv increase in the near surface ozone concentration over tropical Africa. The impact of lightning on surface ozone is negligible, while anthropogenic emissions yield a maximum of 7 ppbv increase in the annual-mean surface ozone concentration over Nigeria, South Africa and Egypt. Our results show that biogenic emissions are the most important African emission source affecting total tropospheric ozone. The influence of each of the African emissions on the global tropospheric ozone burden (TOB) of 384 Tg yields about 9.5 Tg, 19.6 Tg, 9.0 Tg and 4.7 Tg for biomass burning, biogenic, lightning and anthropogenic emissions emitted in Africa respectively. The impact of each of these emission categories on African TOB of 33 Tg is 2.5 Tg, 4.1 Tg, 1.75 Tg and 0.89 Tg respectively, which together represents about 28% of the total TOB calculated over Africa. Our model calculations also suggest that more than 70% of the tropospheric ozone produced by each of the African emissions is found outside the continent, thus exerting a noticeable influence on a large part of the tropical troposphere. Apart from the Atlantic and Indian Ocean, Latin America experiences the largest impact of African emissions, followed by Oceania, the Middle East, Southeast and south-central Asia, northern North America (i.e. the United States and Canada), Europe and north-central Asia, for all the emission categories.
Keywords: African Research